2022
DOI: 10.1007/s11947-022-02884-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effectiveness of a Vertical Centrifugation System Coupled with an Inert Gas Dosing Device to Produce Extra Virgin Olive Oil

Abstract: Recent decades have seen the development of many effective and innovative technologies for extra virgin olive oil (EVOO) extraction. Various solutions have been proposed to remove dissolved oxygen from the oil. Given these issues, we have designed and developed a system that can be added to the centrifuges that are already used in the olive oil industry. The system reduces the oxidative impact through the release of a technical gas inside the separator, and consequently delays the onset of defects related to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Finally, several studies of virgin olive oil production have been carried out in real or pilot mills using a decanter centrifuge, [ 13,38–41 ] and they typically measure VOCs as in the present work. While conducting trials at industrial scale can improve the reliability of the obtained results, it creates several other problems, notably with respect to obtaining and randomizing oil samples, controlling process variables, running a large number of replicates, etc.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, several studies of virgin olive oil production have been carried out in real or pilot mills using a decanter centrifuge, [ 13,38–41 ] and they typically measure VOCs as in the present work. While conducting trials at industrial scale can improve the reliability of the obtained results, it creates several other problems, notably with respect to obtaining and randomizing oil samples, controlling process variables, running a large number of replicates, etc.…”
Section: Resultsmentioning
confidence: 99%
“…[30,37] In the latter scenario, olive batches may be very small, which increases the risk of obtaining a product that contains a significant percentage of oil from a cultivar other than that declared on the label. Finally, several studies of virgin olive oil production have been carried out in real or pilot mills using a decanter centrifuge, [13,[38][39][40][41] and they typically measure VOCs as in the present work. While conducting trials at industrial scale can improve the reliability of the obtained results, it creates several other problems, notably with respect to obtaining and randomizing oil samples, controlling process variables, running a large number of replicates, etc.…”
Section: Quantitative Qualitative and Experimental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23 ] This aspect was also recently modeled. [ 24 ] The feasibility of applying blanketing to the vertical separator was recently confirmed by Angeloni et al., [ 25 ] while Masella et al. [ 26 ] showed that pumping the olive paste during the extraction process also affects the DO concentration in the extracted oil.…”
Section: Introductionmentioning
confidence: 99%
“…The role of oxygen during crushing on volatile, phenol and sensory properties has been stated. In particular, the increase of oxygen during the crushing has been described by [11,[28][29][30][31][32][33]; and reducing by Vezzaro et al [19] and Sánchez-Ortiz et al [12]. The present work aims to investigate the role of oxygen not only on volatile compounds and phenols, but also on quality parameters and other relevant minority compounds such as: chlorophylls and carotenoid pigments and tocopherol during crushing and malaxation at industrial scale in `Picual´ cultivar, one of the most widely distributed strains in the world.…”
Section: Introductionmentioning
confidence: 99%